Environmental Influences on the Distribution of Mangroves on Bahamas Island - Strauch, Ayron M; Cohen, Sam; Ellmore, George S (Journal of Wetlands Ecology, 2012)
Mangrove forests provide valuable ecosystem services but are declining in many tropical locations. The abundance of mangrove species in coastal fringe forests is related to biotic processes such as species succession or competition and abiotic factors, including nutrient availability, physiochemical water quality, soil composition, and tidal inundation. We examined the abundance of Rhizophora mangle and Avicennia germinans relative to environmental factors, including porewater chemistry, soil substrate, and distance from the ocean, on Bahamas Island. In this system, R. mangle were primarily found in litter-dominated soils and abundances were positively related to distance from the ocean, while A. germinans was only found in sandy soils closest to the ocean. Although phosphate, alkalinity, and salinity in porewater did not explain the distribution of species, free chloride varied significantly with distance from the ocean. These results suggest that soil conditions and tidal inundation may help determine the distribution of mangrove species on Caribbean islands. DOI: http://dx.doi.org/10.3126/jowe.v6i0.6081 J Wet Eco 2012 (6): 16-24